The Impacts of Covid-19 Pandemic to Hospitality Business in Luang Prabang City - SISAVANH, Orlathai; SIFONGXAY, Sangthong; LATTANASOUVANHNAPHONH, Champa; SAYYAVONG, Somkhuan; MIXAYKONE , Khanthaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The impact of the novel coronavirus pneumonia (Covid-19) on the tourism service company in Luang Prabang, according to research. The project aims to: 1) investigate the influence of the novel coronavirus pneumonia pandemic (Covid-19) on the service industry in Luang Prabang city. 2) To examine how service industry owners feel about the application of government regulations following the unique coronavirus pneumonia epidemic (Covid-19). 3) Suggest policies for the reorganization of service enterprises in Luang Prabang. The study method is quantitative, the sample group is 283 tourism service business operators in Luang Prabang city. Data was collected through a set of questionnaires that were distributed among 385 Entrepreneurs in the tourism industry. The obtained data was then analyzed by using the Statistical Package of the Social Sciences Program. According to descriptive statistics, the data analysis tools used were percentage, mean and standard deviation. The research's findings showed that the majority of informants are male, between the ages of 30 and 40, with a bachelor's degree, a personal business model, a small business size, the primary source of funding for the business being personal funds, the type of service business being a temporary business, the duration of the business being less than five to ten years, and the average monthly revenue in the business (prior to the Covid-19 outbreak) being between 10,000,000-50,000,000 kip. After the Covid-19 epidemic, the average monthly business is less than 10,000,000 kip. The study's findings on the new corona virus's (Covid-19) effect on the service industry in Luang Prabang revealed that: overall, the service industry in Luang Prabang has been adversely impacted by the epidemic of the new corona virus (Covid-19) on a large scale, with both the social and economic effects being severe. According to the study's findings, service businesses in Luang Prabang have a generally positive opinion of the government's implementation of its policy to lessen the effects of the new pneumonitis epidemic (Covid-19). The public and private sectors must work together to implement different policies and regulations to lessen the impact, jointly develop consistent regulations and policies, and appropriately grant access to various businesses in order to adapt the service industry in the future.